FUN LEARNING FOR ENGLISH COMMUNICATION: A COMMUNITY ENGAGEMENT PROGRAM IN AN ISLAMIC BOARDING SCHOOL - Agwin Degaf; Zainur Rofiq (Journal of Social Outreach, 2026)
English communication remains a persistent challenge for students in Islamic boarding schools, where language learning is often shaped by strong disciplinary structures but still limited by speaking anxiety, low confidence, and insufficient opportunities for meaningful interaction. Within the broader discussion of English language teaching in pesantren, this issue is important because communicative difficulties are frequently addressed through formal instruction and language regulation, while the role of enjoyable, interaction-based learning remains less systematically explored. This article aims to examine how a fun learning workshop can foster students’ engagement, speaking confidence, and willingness to use English more actively in a boarding school environment. The article is based on qualitative data gathered through classroom observation, semi-structured interviews with student participants, and informal feedback from language coordinators involved in the program. The data were reviewed descriptively and interpreted thematically to identify recurring patterns in students’ responses to interactive learning activities. The study shows that fun learning activities encouraged more active participation, reduced students’ hesitation to speak, and helped them experience English as a practical means of communication rather than merely a formal subject. The workshop also generated practical ideas for sustaining English use through peer interaction and dormitory-based language supervision. These findings suggest that communicative English programs in Islamic boarding schools can be strengthened by integrating interactive and context-responsive activities into regular language practice, while future studies may examine the longer-term impact of such interventions across different pesantren settings.